(untitled) (Brazilian Journal of Radiation Sciences, 2018)
Photon beams produced in large linear accelerators are widely used in medicine for the treatment of cancer. Nevertheless, the use of these medical purpose machines in radiotherapy bring some interesting questions as for example how to evaluate the thicknesses of the walls of the facility room housing them in order to guarantee that their vicinities do not receive a radiation dose above the permissible levels. The aim of work is to present a simplified general formalism for the estimation of wall thicknesses of a facility room housing linear accelerators that generate photons with energies in the range 4-30 MeV and using ordinary concrete as the material of shielding. A computer code based on FORTRAN programming language was developed in order to handle with all the input parameters. The roof thickness was calculated according to the skyshine approach, and the overall results have shown a lower total volume and associated cost of concrete shielding as compared with the primary approach.